PREVALENCE OF BLATEM, BLASHV, AND BLACTX-M GENES AMONG ESBL-PRODUCING ESCHERICHIA COLI ISOLATED FROM THE BLOOD SAMPLES OF ICUS PATIENTS OF UNIVERSITY HOSPITALS IN SANA’A CITY, YEMEN - Al-Tahish, Ghamdan Ahmed Ali; Al-Yosaffi, Eshtiaq A; Othman, Arwa Mohammed; Al-Shamahy, Hassan Abdulwahab; Al-Haddad, Ahmed Mohammed; Al-Moyed, Khaled Abdulkarim; Al-Shawkany, Abdul-Al-Raoof Mohammad (Universal Journal of Pharmaceutical Research, 2024)
Aim and Objective: With the emergence of organisms such as Enterobacteriaceae that produce extended-spectrum β-lactamase (ESBL), which are resistant to multiple medications (multidrug-resistance), concerns about how best to treat infections have significantly increased. The current study examined the molecular features of ESBL in clinical isolates of Escherichia coli that resulted in bloodstream infections as well as the pattern of antibiotic resistance to gather useful data on the infection’s epidemiology among Yemeni ICU patients. Subjects and methods: A cross-sectional study was conducted on sepsis patients admitted in intensive care units at four hospitals in Sana’a, Yemen, between January, 2021 and April, 2022. Blood cultures were used on patients suspected of having sepsis. Standard laboratory procedures were then used to isolate and identify possible bacterial infections, and the disk diffusion method was used to test for microbial susceptibility. All strains were tested for Extended Spectrum Beta-Lactamase (ESBL) production using the Modified Double Disc Synergy Test (MDDST). Following analysis, polymerase chain reaction, β-lactamase genes (blaTEM, blaSHV, and blaCTX-M) were identified. Results: The results of the conventional PCR experiment revealed that 33.3% of the blaCTX-M genes, 0.0% of blaSHV, and 100% of blaTEM were present in the strains of ESBL-producing E. coli that were collected. It was discovered that the E. coli isolates’ patterns of antibiotic resistance to 23 different antibiotics differed greatly. The bulk of the E. coli isolates were found to be multi-drug resistant (MDR). Furthermore, MDR characteristics were observed in 85% of E. coli isolates. Conclusion: Control and surveillance of antibiotic resistance depend on an understanding of the resistance genes and patterns of antimicrobial resistance of bacterial pathogens within a given geographic area. The current study’s findings showed that MDR was very common. According to the current study’s findings, TEM was significantly more common than other ESBL gene types. Peer Review History: Received: 6 October 2023; Revised: 7 November; Accepted: 28 December; Available online: 15 January 2024 Academic Editor: Dr. A.A. Mgbahurike , University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Reviewers: Dr. Rola Jadallah, Arab American University, Palestine, rola@aauj.edu Dr. Wadhah Hassan Ali Edrees, Hajja University, Yemen, edress2020@gmail.com